2023
DOI: 10.1590/1806-9282.20230740
|View full text |Cite
|
Sign up to set email alerts
|

Use of the laser in the pilonidal sinus alone or in combination with phenol

Azad Gazi Şahin,
Erman Alçı

Abstract: OBJECTIVE:We investigated the effectiveness of combining laser treatment with phenol in the management of pilonidal sinus. METHODS:We present here a retrospective analysis of patients with pilonidal sinus disease who were treated in the general surgery clinic of the Balikesir University Hospital between October 2019 and February 2022. RESULTS: Recurrence was observed in three patients (13.6%) in the laser treatment group and one patient (4.8%) in the laser-phenol treatment group after the fourth month. Notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…This procedure involves creating a small incision and using the laser fiber to seal the sinus tract [27]. Studies have reported impressive complete healing rates of up to 94.4% with laser treatment alone [28]. The exploration of combined laser therapy with phenol application has also shown promise.…”
Section: Laser Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure involves creating a small incision and using the laser fiber to seal the sinus tract [27]. Studies have reported impressive complete healing rates of up to 94.4% with laser treatment alone [28]. The exploration of combined laser therapy with phenol application has also shown promise.…”
Section: Laser Therapymentioning
confidence: 99%
“…In a retrospective study, the laser-phenol treatment group exhibited a lower recurrence rate (4.8%) than laser treatment alone (13.6%), albeit without statistical significance. Additionally, the laser-phenol group demonstrated a higher complete healing rate (95.5%) in contrast to the laser-only group (91.7%) [28]. Laser therapy presents several advantages, including minor wounds, mild postoperative discomfort, and a short recovery period, enabling patients often to resume work within a week post-surgery [27].…”
Section: Laser Therapymentioning
confidence: 99%
See 1 more Smart Citation